Oxygen vacancy induced Pt-decorated MOF photocatalyst for hydrogen production. (30th April 2023) - Hussain, Muhammad Bilal; Kang, Bokai; Cheng, Xingxing; Ma, Chunyuan; Wang, Xuetao; Mehmood, Rashid; Iqbal, Sikander
Abstract: The photocatalytic performance has remained challenging due to the rapid recombination of photoexcited electron-hole (e-h) pairs. To overcome this problem, creating oxygen vacancies on the surface of semiconductors has been an effective strategy. Herein, we report the effects of oxygen vacancies (Ov) on photocatalytic HER performance of Pt nanoparticles (NPs) anchored on UiO-66-NH2 . In contrast, under the same amount of Pt NPs, UiO-66-NH2 with high oxygen vacancies (denoted as Pt/UN-Ovh) exhibit superior photocatalytic H2 generation than the catalyst with low oxygen vacancies (denoted as Pt/UN-Ovl) under visible-light irradiation. Based on the experimental characterization and theoretical calculations, the high oxygen vacancies not only stabilize the Pt NPs on the substrate (UiO-66-NH2 ), but also develop the strong interaction between Pt NPs and support thereby Pt NPs traps more electrons from substrate and provides protons for H2 production inhibiting the electron-hole recombination. This work provides novel strategy for enhancing the photocatalysts performance of MOF based materials. Graphical abstract: Image 1 Highlights: Effects of oxygen vacancies (Ov) of MOFs on photocatalytic HER. Pt/UN-Ovh exhibited 3 times higher performance than Pt/UN-Ovl catalyst. Vital role of Oxygen vacancies (Ov) to develop strong metal-support interaction.